The helix‐inversion mechanism in double‐stranded helical oligomers bridged by rotary cyclic boronate esters. Issue 23 (16th May 2019) - Hayashi, Taku; Lee, Ka Hung; Iida, Hiroki; Yashima, Eiji; Irle, Stephan; Hijikata, Yuh
Abstract : Attracted by the numerous regulatory functions of double‐helical biopolymers such as DNA, many researchers have synthesized various double‐helical systems. A recently synthesized double‐stranded helical oligomer covalently bridged by rotary boronate esters (BBDD) was shown to undergo helix‐inversion that might serve as platform to design rotor systems. However, the detailed helix‐inversion mechanism could not be investigated experimentally. Direct molecular dynamics simulations based on density‐functional tight‐binding energies and gradients computed on‐the‐fly reveal that disentanglement to the unraveled form and following exchange of the twisted terminal trimethylsilyl (TMS) groups are prerequisites for the observed helix‐inversion. The potential of mean force confirms that the originally assumed "concurrent" rotation of the boronate esters and the helix‐inversion involves shorter time scale "step‐wise" processes, triggered by the disentanglement and exchange of the TMS groups. These results indicate that inversion dynamics of double‐helical molecules such as BBDD may be controllable by chemical fine‐tuning of the terminal groups. © 2019 Wiley Periodicals, Inc. Abstract : A helical oligomer consisting of covalently bridged two strands shows helix‐inversion where unclear dynamic process has been remained. Molecular dynamics simulations with density‐functional tight‐binding method revealed that disentanglement and following exchange of terminal trimethylsilyl groups are prerequisites of helix‐inversion. The potential of mean force uncovered decreasing energy barrier of helix‐inversion after the disentanglement and exchange. This result suggests that helix‐inversion dynamics is a "step‐wise" process triggered by the disentanglement and exchange.